Culture Views Of Metalhead "Soloensis Band" Through Semiotics Ferdinand De Saussure - Wulansari, Shafa Bidhari (JIKE : Jurnal Ilmu Komunikasi Efek, 2023)
Abstract This research aims to make the phenomenon gap interesting for researchers and will be used as a focus of research in a semiotic perspective to understand the meaning of hardcore cultural representations. The object of this study shows that music with the metal and rock genres can also influence patterns of symbolic communication (moshing) and traditions in a culture, and the subjects of this research are the band Soloensis as a band with the metal genre, and teenagers who do moshing. The phenomenon of the development of genres in music and the existence of subcultures of several genres, one of which is the hardcore subculture in the metalhead community in the metal music genre and the like, which is marked by the large number of music concert events (gigs). Quoted from the Indonesiana.id article, after the post-pandemic period, there have been many lively music concerts and national music concerts, namely the Synchronize Festival, which mostly features bands with the metal or rock genre, and have many fans. Differences in styles, trends and traditions carried out by this subculture are among metalheads who have their own culture and traditions, where metalheads enjoy concerts by carrying out moshing actions. This study focuses on using Ferdinand De Saussure's semiotic perspective on symbols and meanings in hardcore culture performed by metalheads in concerts with interpretation communication theory. From the semiotic perspective in this study there are 2 conclusions, namely the meaning of the signifier and the meaning of the signified.